Possible new method to improve detection of diabetic retinopathy: Polaroid non-mydriatic retinal photography. Issue 6504 (2nd November 1985) - Ryder, R E; Vora, J P; Atiea, J A; Owens, D R; Hayes, T M; Young, S
Abstract : Two retinal cameras (Canon CR2 45NM and CR3 45NM) have recently become available and are capable of producing an instant colour photography of a 45 degree field of retina, including the macula and optic disc, without dilatation of the pupils being necessary. The ability of each camera to detect diabetic retinopathy was compared with that of doctors in diabetic clinics using ophthalmoscopy during busy clinic hours. The CR3 was found to be considerably superior to the CR2 in terms of quality of photograph because it can use a smaller pupil. Overall, the detection rate of the camera was more than four times higher than that of ophthalmoscopy through undilated pupils and more than twice as high as that of ophthalmoscopy through dilated pupils. Lesions missed by ophthalmoscopy but detected by the camera included soft exudates and circinate rings of hard exudates, sometimes encroaching on the macula. Though various aspects of this system of screening for diabetic retinopathy, in particular its ability to detect new retinal vessels, have not yet been assessed, the system may prove beneficial in the detection and monitoring of diabetic retinopathy.